2020
DOI: 10.1021/acs.joc.0c00936
|View full text |Cite
|
Sign up to set email alerts
|

Copper-Catalyzed Preparation of Benzo[3,4]indolo[1,2-b]isoquinoline-8-ones and Photoluminescence Exploration

Abstract: A facile synthesis of benzo­[3,4]­indolo­[1,2-b]­isoquinolin-8-ones is described. Under copper catalysis, the reaction proceeds with a high efficiency and a broad reaction scope. A deuteration experiment shows that the KIE value is 2.85. From the results on mechanism studies, copper-catalyzed C–H activation, intramolecular cis-addition of alkynes, and reductive elimination are involved. Moreover, this skeleton is indeed a new fluorophore, and its photophysical properties are also investigated.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
13
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 18 publications
(13 citation statements)
references
References 52 publications
0
13
0
Order By: Relevance
“…The crystal structure of 2[B(C 6 F 5 ) 3 ] 2 showedt hat two B(C 6 F 5 ) 3 units sit above and below the plane of the amide-embedded coronene skeleton with the OÀBd istance of 1.571 (5) .A sa result of this complexation, the amide-embeddedh exagon ring itself was deviated from the plane to am ore extentc ompared to that of parent 2.I mportantly,t he amide NÀCb ond was shortened to be 1.419(5) ,w hile the amide CÀOb ond length is elongatedt o1 .308(5) ,i ndicative of the increased aromaticity by the complexation with B(C 6 F 5 ) 3 .I ndeed, the NICS(1) zz value of the amide-embeddedr ing, calculated using the crystal structure at the same level as that for 2',w as more negative value of À21.4 ppm compared to those (À17.6 and À16.9 ppm) in 2' (Figure S11).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The crystal structure of 2[B(C 6 F 5 ) 3 ] 2 showedt hat two B(C 6 F 5 ) 3 units sit above and below the plane of the amide-embedded coronene skeleton with the OÀBd istance of 1.571 (5) .A sa result of this complexation, the amide-embeddedh exagon ring itself was deviated from the plane to am ore extentc ompared to that of parent 2.I mportantly,t he amide NÀCb ond was shortened to be 1.419(5) ,w hile the amide CÀOb ond length is elongatedt o1 .308(5) ,i ndicative of the increased aromaticity by the complexation with B(C 6 F 5 ) 3 .I ndeed, the NICS(1) zz value of the amide-embeddedr ing, calculated using the crystal structure at the same level as that for 2',w as more negative value of À21.4 ppm compared to those (À17.6 and À16.9 ppm) in 2' (Figure S11).…”
Section: Resultsmentioning
confidence: 99%
“…Herein we focus our attention on employing an amide bond as an isosteric replacement of aC =Cd ouble bond (Figure 1a). [5][6][7] The amide CÀNb ond has ap artial double bond character, which corresponds to one third of the p bond energy of the C=Cb ond, which should have ad irect impact on the aromaticity of the PAHs keletons.M oreover,t he amide carbonyl group would generatealocal dipole to the skeleton and therebyg ive rise to the polarity-dependent character of the absorption and fluorescent properties. There are two ways to introducet he amide bond into PAHs:e ither replacing the double bond at the outer K-region, or integration of the amide moiety to the peripheralc oncaver egion in af ashiont hat the inner angular carbon atom is replaced with the amide nitrogen atom with three distinct CÀNb onds.…”
Section: Introductionmentioning
confidence: 99%
“…The KIE results indicated that the C–H bond cleavage step was not the rate-determining step in the formation of 1s . Notably, a distinctive reaction pathway from that of our previous results was involved herein, although similar starting materials were employed …”
Section: Resultsmentioning
confidence: 99%
“…Copper is an abundant, non-expensive, and relatively nontoxic transition metal, and therefore copper-mediated reactions for direct functionalization of C-H bonds have emerged as promising tools for development of more sustainable methods for the synthesis of fine chemicals. Reactions involving copper-medi-ated C-H activations allow for a direct insertion of functional groups in unreactive C-H bonds and the formation of carbon-carbon bonds without the requirement of prefunctionalized substrates, which allow for shorter synthetic routes or latestage modifications of structurally complex compounds [304][305][306][307][308][309][310][311][312]. However, the development of efficient methods can be challenging due to the requirement of directing groups and control of selectivity.…”
Section: Copper-catalyzed C-h Activationmentioning
confidence: 99%
“…On the other hand, such heterocyclic moieties present in bioactive compounds, or their synthetic intermediates may eventually play the role of a directing group, thus providing an opportunity for convenient and straightforward transformations based on metal-mediated C-H activation [314]. Many methods potentially useful for the synthesis or modification of bioactive compounds based on copper-promoted activation of C-H bonds in (hetero)arenes have been reported in the last years, including methods for the formation of C-C [304][305][306][307][308][309][310][311][312], C-X [315][316][317][318][319], C-N [305,[320][321][322][323][324], C-O [325][326][327][328][329][330], and C-S [324,331,332] bonds. Some of these methods are highlighted herein.…”
Section: Copper-catalyzed C-h Activationmentioning
confidence: 99%